OPTIMIZING THE ROLE OF RECEIVING IN THE SMOOTH OPERATIONAL OF GOODS IN THE ONE LEGIAN - Whenyca Marranitha, I Dewa Ayu; Crisna Wijaya, Gede (LPPM Univ. Ibn Khaldun Bogor, 2023)
The tourism industry is one of the most influential industries for the economy in Bali. With its potential to be a driving force for entrepreneurs in Bali to develop businesses, one of which is the room or hotel rental service business. To support the smooth operation of goods at the hotel, all goods that enter the hotel for operational purposes go through the Receiving section for data collection and supervision. The goods received by the Receiving section are items requested from each department in the hotel that have previously been purchased by the procurement department or the Purchasing section. The Receiving Officer at The One Legian has been in accordance with its role, namely there is a relationship between the Receiving role of the smooth operation of goods. In addition, to support the work of the Receiving officer, the goods that arrive at the hotel must comply with orders supported by Purchase Orders, Purchase Requests and Market Lists.